Defining expected cost for the air conditioning to avoid a price spike of electricity market under DSR model - Marwan, M.; Ledwich, G.; Ghosh, Arindam (Institute of Electrical and Electronics Engineers ( IEEE ), 2013)
This work presents a demand side response model (DSR) which assists small electricity consumers, through an aggregator, exposed to the market price to proactively mitigate price and peak impact on the electrical system. The proposed model allows consumers to manage air-conditioning when as a function of possible price spikes. The main contribution of this research is to demonstrate how consumers can minimise the total expected cost by optimising air-conditioning to account for occurrences of a price spike in the electricity market. This model investigates how pre-cooling method can be used to minimise energy costs when there is a substantial risk of an electricity price spike. The model was tested with Queensland electricity market data from the Australian Energy Market Operator and Brisbane temperature data from the Bureau of Statistics during hot days on weekdays in the period 2011 to 2012. © 2013 Australasian Committee for Power Engineering (ACPE).